Neuregulin 4: A Key Regulator in Suppressing Lung Adenocarcinoma Progression - Shufan Zhang BMed; Tianhan Xu BMed; Simeng Li BMed; Liming Tang MD; Dongmei Wang PhD (Technology in Cancer Research & Treatment)
Introduction: Lung adenocarcinoma remains a significant public health concern, necessitating novel therapeutic approaches. Neuregulin 4 (NRG4), a secreted protein of the epidermal growth factor family, is recognized for its roles in metabolic regulation and anti-inflammatory processes, suggesting therapeutic potential across various diseases. However, its specific function in lung adenocarcinoma progression is not well elucidated. Methods: We utilized The Cancer Genome Atlas (TCGA) database to examine correlations between NRG4 expression, epithelial-mesenchymal transition (EMT)-related genes, and overall survival in lung adenocarcinoma patients. The effects of recombinant NRG4 (rNRG4) on cell migration and cancer progression were evaluated through Transwell assays, quantitative PCR, immunofluorescence, and immunohistochemistry. Additionally, a lung adenocarcinoma mouse model (LLC-bearing) was employed to assess the impact of rNRG4 on tumor progression. RNA sequencing of primary tumors was conducted to explore the functional mechanisms underlying rNRG4's effects. Results: Our analysis revealed that NRG4 expression inversely correlates with key molecules involved in cell migration and EMT in lung adenocarcinoma. Treatment with rNRG4 significantly inhibited cell proliferation, migration, EMT, and tumor growth in both in vitro and in vivo models. RNA sequencing indicated that rNRG4 downregulates extracellular matrix (ECM) proteins, and online database analyses confirmed that higher NRG4 expression is associated with reduced ECM levels and improved patient survival. Conclusions: These findings suggest that NRG4 serves as a potential candidate for further investigation for lung adenocarcinoma.